Niger Delta Oil Spill Legal Victory against the Shell Company: The Future of Corporate Environmental Responsibility: Array - Ngwakwe, Collins (Acta Universitatis Danubius. Juridica, 2021)
It is a heinous task for plaintiffs to secure environmental justice against multinational companies’ human right and environmental violation in developing countries. Objective: The objective of this paper is to appraise the current landmark case of environmental pollution victory by the Niger Delta farmers against the Shell Company. Prior work: The prior work reliance is the argument on jurisdiction – which poses environmental justice barrier. Method: the paper is conceptual and reviews the latest decided oil spill case in the Dutch Court of Appeal, the Hague between Niger Delta farmers and the Shell Petroleum Development Company of Nigeria. Findings: it finds that environmental justice by rural poor communities can receive equitable hearing in foreign countries, which are home to the parent company. However, this requires passage of many hurdles – the heavy cost, evidence, and time. It thus requires support of environmental advocacy groups. Implication: the paper highlights that corporate environmental responsibility may not always be escapable based on corporate economic girth and flimsy excuses of local sabotage. It provides an agenda for further analysis and constitutes a recent case for academic studies in corporate governance class in business schools. Value: the paper is one of the first to analyse the future implication of corporate environmental responsibility, which relies on the recent oil spill case at the Dutch Court of Appeal, The Hague.